IMPORTANCE OF PATTERN RECOGNITION RECEPTORS IN THE DEFENSE OD THE HUMAN ORGANISM (CIPEEX, 2025)
The aim of this study was to review the role of pattern recognition receptors in innate immunity.Innate or natural immunity is the body's first line of defense against invading agents and actsquickly to identify and neutralize pathogens. It is made up of physical, chemical and biologicalbarriers, for example, macrophage phagocytes and neutrophils. But, despite being fast, it doesnot have much specificity because it does not have immunological memory and does notpromote genetic recombination of its receptors, which is observed in adaptive immunity, whichis highly specific with high variability of receptors from recombination of VDJ genes. PatternRecognition Receptors (PRR) are molecules present on the surfaces of phagocytes capableof recognizing pathogen-associated molecular patterns (PAMP) and signs of cell damage indamage-associated molecular patterns (DAMP). They are essential for the proper functioningof innate immunity. After recognition of PAMP or DAMP, PRR triggers a series of reactionsthat include the release of cytokines, chemokines, and activation of the complement system,promoting inflammation and triggering immune cells to the site of infection. The main types ofPattern Recognition Receptors are Toll-Like Receptors (TLR), which can be located on the cellsurface (plasma membrane) or in endosomes, and recognize PAMP, such as bacteriallipopolysaccharides (LPS) and viral RNA, initiating the signaling that leads to the production ofcytokines and the participation of different mechanisms in immune defense. NOD-LikeReceptors (NLR) are cytoplasmic receptors, whose function is to act in inflammasomeassembly, signaling transduction, transcription activation and autophagy, and as a keyregulator in apoptosis. RIG-I-Like Receptors (RLR) are located in the cytoplasm, and act ascytosolic viral RNA sensors that activate antiviral responses. Scavenger Receptors located onthe surface of macrophages and dendritic cells, they play a crucial role in the detection andremoval of pathogens, damaged cells and potentially harmful molecules, being important in defending against infections and maintaining tissue homeostasis. C Type Lectin Receptors(CLR) recognize carbohydrates present in fungi and other pathogens on the cell surface. Thus,RRPs have great variability and the ability to recognize common molecular patterns ininfectious agents, seeking the participation of innate immunity in defense, in addition tofavoring connections with acquired immunity, maximizing the body's protection againstaggressors.
Keywords: prr; pathogens; pamp; damp; share